Army Soldiers’ Knowledge of, Attitude Towards, and Preventive Behavior Towards Tuberculosis in Korea - Choi, Yun (Osong Public Health Res Perspect, 2018)
OBJECTIVES: The aim of this study was to gather information about Korean Army soldiers’ attitude towards tuberculosis to enable the development of an informed educational program and potential intervention plans. METHODS: There were 500 male soldiers serving in the Korean Army who responded to questionnaires regarding knowledge of, attitudes towards, and preventive behavior towards tuberculosis. The questionnaires were collected between September 10 until October 1, 2014. Participants’ characteristic that influenced differences in knowledge, attitudes, and preventive behavior towards tuberculosis were compared by t test. Variables that influenced preventive behavior were identified by multiple regression analysis. RESULTS: The mean scores assessing knowledge of, attitude, and preventive behavior towards tuberculosis were 11.64 (± 4.03) out of 20 points, 3.21 (± 0.38) out of 4 points, and 2.88 (± 0.42) out of 4 points, respectively. Non-smokers were more knowledgeable about tuberculosis than smokers. Participants who had family or friends with tuberculosis had better knowledge and a more productive attitude to tuberculosis. Participants who were educated or obtained information about tuberculosis, received better scores in all areas of knowledge, attitude and preventive behavior compared to other participants. Non-smoking, family or friends who have had tuberculosis, obtaining information about tuberculosis, and positive attitudes towards treatment and preventive education had an explanatory power of 24.6% with regard to preventive behavior against tuberculosis. CONCLUSION: More relatable, systemized education should be provided regularly to improve soldiers’ knowledge of, attitudes towards, and prevention against tuberculosis in the Republic of Korea Army.